(3TQM GdeYdbGJ GdSHYs - (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s ((3jMji Hf YeGQ GdaGdi s)
(3ChdgG (B:s
(3bGd GdbGVi GdCeGe CHh YHO Gddg gPG TQM GdbUGFO GdSHY , C(B/(3djJg Ydi MO GdEjLGR hGdGNJUGQ Ydi MSH eG GbJQM Ydi s
(3BNQgG (B:s
(3hgh GdQH hGdTgjO Ydi jhe GdMjGQjf hGdHdGA HdGA Je GdcJGH HMeO Gddg s
(3ChQGbgG ai BNQgG eVWQHg JMJGL Edi JQjHs
(3HgG CKQ QWhHg hHYV JbWjY hJQbjYs
(3fSNI QGHYI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs